Book review of: Alcohol in Latin America: A Social and Cultural History. Edited by Gretchen Pierce and Áurea Toxqui. Tucson: University of Arizona Press, 2014 (2015)
Food and alcohol history have in recent decades won academic attention and have demonstrated their potential as privileged gateways for thinking about broad historical questions. Focusing on fermented and distilled beverages, this collection of stimulating essays aims precisely at using “alcohol as a way to understand bigger topics within Latin American history, such as identity, ethnic and communal bonding, race, class, gender, power relations, state-building, and resistance” (p. 9). The editors, both experts on the history of alcohol in Mexico, also intended to compile writings that cover a broad regional and temporal spectrum. The volume is organized chronologically and is divided into three parts, covering respectively the pre-Hispanic and colonial periods, the long nineteenth century, and the twentieth and twenty-first centuries. The introduction presents a well-developed historiographical overview of this subject, including the history of drugs.